Rapid synthesis: Enhancing health promotion and disease prevention in networked primary care - Mattison, CA; Belal, A; Scallan, Eilish; Wilson, MG (My University, 2018)
An assessment of what is known about health promotion and disease prevention in networked primary care. The rapid synthesis was conducted to address a question posed by a health system policymaker or stakeholder to the McMaster Health Forum’s Rapid Response program.
Keywords: health promotion; disease prevention; network; primary care